Examining the Effects of Impulsivity, Intolerance of Uncertainty, and Smartphone Management Styles on Smartphone Addiction with the Mediating Role of Warm Executive Functions - Asheri, Maryam; Ghodsi, Parvaneh; Ghasemi, Masoud (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: The increasing use and influence of mobile phones on individuals’ daily habits, behaviors, and lifestyles have brought significant changes and may cause serious and important problems in people’s lives. This study investigated the impact of variables such as impulsivity and intolerance of uncertainty, along with smartphone management styles on smartphone addiction, mediated by warm executive functions. Methods and Materials: The current study was descriptive and correlational. The sample consisted of 722 high school students selected through convenience sampling. Data were collected using the Bianchi and Phillips (2005) Mobile Phone Addiction Questionnaire, the Barratt Impulsiveness Scale (1997), the Intolerance of Uncertainty Scale by Dugas et al. (1998), the Hsieh, Jen, and Chou (2019) Smartphone Management Styles Questionnaire, and the BRIEF Executive Functions Questionnaire (Parent Form) by Gerard et al. (2000). Data analysis was conducted using Structural Equation Modeling (SEM) through AMOS software version 25. Findings: Results indicated significant inverse relationships between impulsivity and warm executive functions (β = -0.74, p < 0.001), impulsivity and smartphone addiction (β = -0.56, p < 0.001), and warm executive functions and smartphone addiction (β = -0.51, p < 0.001). Direct and significant relationships were found between intolerance of uncertainty and warm executive functions (β = 0.66, p < 0.001), intolerance of uncertainty and smartphone addiction (β = 0.73, p < 0.001), and warm executive functions and smartphone addiction (β = -0.51, p < 0.001). Significant inverse relationships existed between management styles and warm executive functions (β = -0.83, p < 0.001), and management styles and smartphone addiction (β = -0.71, p < 0.001). Conclusion: Therefore, it can be concluded that there are relationships between impulsivity, intolerance of uncertainty, and smartphone management styles with smartphone addiction mediated by warm executive functions.